Subversive marginality in Silviano Santiago's Stella Manhattan - Burianova, Zuzana (Romanica Olomucensia, 2016)
The aim of this article is to reflect on marginalised hybrid identity in the novel Stella Manhat‑ tan (1985) by the Brazilian writer Silviano Santiago. The question of identity is discussed in relation to the issues of artistic creation in postmodernity and the political situation during the Brazilian military regime. The article draws on some key concepts in Santiago's essayistic work, such as ``amphibious literature'', ``the postmodern narrator'', ``the astute homosexual'' or ``the space in-between''.
Keywords: military dictatorship; LGBT literature; postmodernity; hybridity; metafiction.